2021
DOI: 10.37766/inplasy2021.1.0050
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of Liuhedan for treating acute pancreatitis A protocol for a systematic review and meta-analysis

Abstract: Condition being studied: Liuhedan is used to treat acute pancreatitis in China. But at present, there is no systematic evaluation report on its therapeutic effectiveness and safety. This protocol aims to reveal the INPLASY 1 International Platform of Registered Systematic Review and Meta-analysis Protocols INPLASY PROTOCOL Effectiveness and safety of Liuhedan for treating acute pancreatitis A protocol for a systematic review and meta-analysis To cite: Cheng et al. Effectiveness and safety of Liuhedan for treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Liuhedan is a well-known TCM prescription developed at our hospital, and its external application to the abdomen effectively relieves pancreatitis inflammation. Previous study has shown that its anti-inflammatory properties inhibit pancreatic secretion and reduce the inflammatory index, and it can improve the immune regulation (18).…”
Section: Discussionmentioning
confidence: 99%
“…Liuhedan is a well-known TCM prescription developed at our hospital, and its external application to the abdomen effectively relieves pancreatitis inflammation. Previous study has shown that its anti-inflammatory properties inhibit pancreatic secretion and reduce the inflammatory index, and it can improve the immune regulation (18).…”
Section: Discussionmentioning
confidence: 99%